Remote calibration of time from NTP servers. (9th November 2018) - Douglas, Rob; Charbonneau, André; Gertsvolf, Marina
Abstract: The Network Time Protocol (NTP), is used for time synchronization in most networked equipment. Seen as capable of 50 ms accuracy or better, it lacks calibration for metrological traceability to its reference, Coordinated Universal Time (UTC). In response to client requests for traceability, the National Research Council (NRC) has begun to monitor NTP servers and document their traceability. We use an NTP calibrator at NRC to measure the time offset of a remote client's NTP server with respect to UTC(NRC). Standard NTP methods and systems are utilized, even for the NTP calibrator in the NRC Time Laboratory. The service aims at broad applicability rather than low uncertainty and can provide traceability to any networked computer that is configured as an NTP server. As with any calibration service, measurement results and the associated uncertainties are reported for each monitored NTP server for quality system records and auditing purposes, and we also make available near-real-time results and alerts.